The Role of psychological capital in crisis management of Imam Hossein (AS) in the event of Ashura - Valiollah Naghi Pourfar; Behzad Mohammadian (پژوهش‌های روانشناختی در مدیریت)
This study aimed to investigate the role of psychological capital in crisis management, according to the tradition of Imam Hossein (AS). The type of research is qualitative that performed by content analysis technique. Data were collected from documents and historical texts. For this purpose our research was performed based on the Mosueh Al-Hossein (AS) book. Analysis was carried out according to the process model of crisis management, with four stages as anticipating a crisis, crisis management plan, organizing and implementing crisis management plan. Finally, it was concluded that, in the pre-crisis stage, Imam (AS) due to issues in the community had come to the awareness that the crisis threatens community and the need for corrective action is necessary in order to achieve the same result as the planning and controlling arrangements for the crisis and its final implementation freed the society from danger. Psychological aspects in all parts of the capital management is deduced and it has some examples such as patience, determination, faith in God and being thankful.